REDUCING SOCIAL ISOLATION AMONG ELDERLY: A LITERATURE REVIEW - Budi Satria (Fakultas Keperawatan-Universitas Syiah Kuala, 2017)
ABSTRACTThe living alone for elderly is undesirable condition that they have to face in their later life. Elderly need a lot of assistance from others which becomes more complicated as their physical and mental conditions are getting degenerative because of aging. Mental health promotion has similarity with health promotion. Both aim to enhancement of well-being rather than on illness and addressing the population as a whole. Using a wide range of strategies such as communication, education, policy development, organizational change, community development and local activities, acknowledge and reinforce the competencies of the population encompass the health and social fields as well as medical services. The aim of this paper is to develop nursing care plan by using theoretical frame work of community nursing mental health promotion. The nursing actions and interventions will be developed based on the program from the existing study in term of reducing social isolation among elderly in community.Keywords: Mental health, community, elderly.